Estrategias lúdicas y el desarrollo de la motricidad fina en niños de la Institución Educativa Inicial N° 263 Datem del Marañón 2024 - Lluliana Tangoa, Púa (2025)
The present research aimed to determine the level of relationship between the application of playful strategies and the development of fine motor skills in children from the Institución Educativa Inicial N°263 Datem del Marañón during the year 2024. To achieve this, a quantitative approach was adopted, with a non experimental, correlational, and cross-sectional design. The population consisted of 92 children aged 3, 4, and 5 years, and the sample was census-based. Data collection was conducted through direct observation, using a guide validated by experts, whose reliability was determined through the Cronbach's Alpha test. The results obtained from the Spearman’s Rho correlation coefficient showed a value of 0.745, with a significance level of 0.05, indicating a positive and significant relationship between the application of playful strategies and the development of fine motor skills in children. Consequently, the null hypothesis is rejected, and the main hypothesis is accepted, confirming that the implementation of playful strategies significantly influences the development of fine motor skills in children from the Institución Educativa Inicial N°263 Datem del Marañón.